Digital Marketing Application Users in Thailand's SME Environment - Dumrongsiri, Aussadavut; Satimanon, Moonthien (International Journal of Economics and Business Management, 2024)
This article aims to uncover the profile of users and non-users of digital marketing applications among Micro, Small and Medium Enterprises (MSMEs) in western Thailand. This study mainly focuses on MSMEs in Perak State. The researchers used a quantitative approach to meet the research objectives. A survey involving 225 business actors of this application in the Central City of Bangkok. A total of 241 survey data that we can analyze descriptively. The results found that out of 241 respondents, 225 were users and 16 were non-users. Chi-square test was conducted for this analysis. The results showed that gender and age drive the adoption of this technology. The majority of users come from social media, followed by e-marketing and digital marketing content. Sharing data, communicating with clients, and promoting and advancement were each found to be the most thought processes for utilizing computerized promoting applications. Many business actors (more than half) are trying to adopt a digital marketing model. It is necessary to update information, branding and promotion related to the use of digital marketing in business so that it can be well received by SME sector entrepreneurs. This finding has implications for the importance of the research community, MSMEs, and policy makers in formulating better strategies for digital marketing applications. The results are expected to provide an overview of how digital technology adoption is facing emerging and innovative market conditions